Nanotechnology Patents in comparison perspective : Patentability Exceptions - Pham, Loan (My University, 2020)
Nanotechnology is presented as the tempestuous technology that holds the promise of universally societal benefits and as a tremendous opportunity to be a primary economic force for the new century. This technology that contributes from an atom by atom is simultaneously bound to bring commencing challenges to the international patent law. Questions may be posed with the large number of patents awarded for nanotechnology inventions and the protection of legal, social, and ethical value. This paper aims to discuss the essential characteristics of nanotechnology, the interaction as well as the conflicts between nanotechnology and patent law; in particular, the primary ethical, social and legal concerns of nanotechnology in the patent system; and whether the established limitations to patentability can be extended to this new technological innovation. Accordingly, the paper will be compared the patent law system of the European countries and Asian countries to show the similarities and the differences in which nanotechnology inventions are patentable in the context of the ethical, social concerns are enormous increases in the two significant areas of the nanotechnological market. From that comparison perspective, the possible reflections will be discussed about personal privacy and eugenic trends. Besides, recommendations to develop the patent system, and the potential future of nanotechnology in each region will also be considered. The research method of this paper includes reviewing existing literature as well as previous research papers from other scholars, then applying the regulation of the patent law to nanotechnology and comparing the current legislation of patent law between regions. Following these methods, the paper will focus on two legal sources: European patent system and Asian patent system regarding patentability exceptions on the grounds of “ordre public” and morality. Other areas, such as scientific background and socio-economic development, are also mentioned in the paper to indicate nanotechnology’s extraordinary potential.
Keywords: nanotechnology, patentability, research and development, exceptions, ethics, “ordre public”, morality, social concerns